2010
DOI: 10.1673/031.010.14117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rain-Fast Bait Stations Versus Foliar Bait Sprays for Control of Oriental Fruit Fly,Bactrocera dorsalis, in Papaya Orchards in Hawaii

Abstract: Bait stations represent an environmentally friendly attract-and-kill approach to fruit fly population suppression. Recently a novel, visually attractive, rain-fast bait station was developed in Hawaii for potential use against multiple species of pestiferous fruit flies. Here, we compared the efficacy of GF-120 NF Naturalyte Fruit Fly Bait applied either as foliar sprays or onto bait stations in reducing female oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae), population density and leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…This was demonstrated by Putruele and Mouqués (2007) with C. capitata in Argentina and by Piñero et al (2010) with B. dorsalis in papaya orchards in Hawaii. Likewise, in area-wide applications the use of bait stations to suppress high density populations in reservoirs has proven effective.…”
Section: Conclusion and Future Research Needsmentioning
confidence: 64%
See 3 more Smart Citations
“…This was demonstrated by Putruele and Mouqués (2007) with C. capitata in Argentina and by Piñero et al (2010) with B. dorsalis in papaya orchards in Hawaii. Likewise, in area-wide applications the use of bait stations to suppress high density populations in reservoirs has proven effective.…”
Section: Conclusion and Future Research Needsmentioning
confidence: 64%
“…Its performance relative to other bait stations has not been assessed in formal studies. Papaya Leaf Mimics Piñero et al (2009aPiñero et al ( , 2010 demonstrated the potential of bait spray applications of GF-120, when used in combination with other management techniques, in achieving a low fruit fly prevalence area in papaya orchards in Hawaii. However, high levels of rainfall affect the efficacy of bait sprays.…”
Section: Bactrocera Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a bait station for attraction and control of oriental fruit fly (Bactrocera dorsalis (Hendel, 1912)) was recently implemented (Piñero et al, 2010). Such attract-and-kill bait stations have the advantage over foliar applications, because the insecticidal bait is protected from weather conditions.…”
Section: Plant Protection Against Olive Flymentioning
confidence: 99%